2021
DOI: 10.3390/su132313468
|View full text |Cite
|
Sign up to set email alerts
|

Local Community Satisfaction toward Tourism Development in Pushkar Region of Rajasthan, India

Abstract: Satisfaction of local residents is one of the key factors in responsible and sustainable tourism development. It helps tourism planners and policymakers in effective and strategic utilization of tourism resources. The present study investigates local residents’ satisfaction level toward sustainable tourism development through economic, socio-cultural, and environmental development. In order to achieve the goal of the study, one-sample t-test, regression analysis, and Structural Equation Modeling (SEM) were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…Tourists, residents, and tourism stakeholders are the moral and legal stakeholders in the tourism sector who determine and conduct the entire tourism system at all levels, and tourism cannot develop with their active participation. Therefore, expectations and perceptions of tourists [111], residents [112], and stakeholders [113] are very crucial to investigating any new concept, trend, or innovation in tourism, before and after their applications. The same has been examined in this particular study regarding the IoT and its technologies [114].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Tourists, residents, and tourism stakeholders are the moral and legal stakeholders in the tourism sector who determine and conduct the entire tourism system at all levels, and tourism cannot develop with their active participation. Therefore, expectations and perceptions of tourists [111], residents [112], and stakeholders [113] are very crucial to investigating any new concept, trend, or innovation in tourism, before and after their applications. The same has been examined in this particular study regarding the IoT and its technologies [114].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The results of the research show similarities with the studies evaluating the effects of satisfaction with tourism development over support for tourism development (Uslu et al, 2020;Ward & Berno, 2011). Maintaining the residents' satisfaction with tourism development in this process depends upon preservation and promotion of local culture, cuisine and environment (Tiwari, Tomczewska-Popowycz, Gupta, & Swart, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The interplay of these dimensions is crucial in ensuring responsible and sustainable tourism practices. Studies have shown that the economic, socio-cultural, and environmental aspects collectively impact and lead to responsible and sustainable tourism development (Tiwari et al, 2021). Furthermore, research indicates that the positive perception of residents towards tourism development, along with its economic, socio-cultural, and environmental impacts, plays a significant role in supporting sustainable tourism (Sonuç, 2020).…”
Section: Basic Concepts Of Sustainable Tourism Developmentmentioning
confidence: 99%
“…Sustainable tourism policies play a vital role in addressing global environmental and development challenges (Guo et al, 2019). The impact of socio-cultural, economic, and environmental factors significantly influences sustainable tourism development (Tiwari et al, 2021). Sustainable tourism emphasizes the need to balance environmental, economic, and socio-cultural aspects in the long run (Nazneen et al, 2021).…”
Section: Challenges In Sustainable Tourism Developmentmentioning
confidence: 99%